Numerical and experimental analysis of impinging synthetic jets for cooling a point-like heat source - Glowienko, Robert; Derlien, Hans; Ertunc, Özgür; Delgado, Antonio (Journal of Heat Transfer-Transactions of the Asme, 2018)
High power light emitting diodes (LEDs) being used for low and high beam in automotive lighting need active cooling of their heat sinks by radial or axial fans. But the moving elements of the fan cause abrasion, noise, and high energy consumption. Synthetic jets can replace conventional fans with their disadvantages and allow the directed cooling of LEDs. Therefore, in this paper, flow and heat transfer characteristics of impinging synthetic jets are investigated numerically and experimentally as an alternative to cooling LEDs with fans. It is shown that the impact plate brings forward the laminar-Turbulent transition of the jets temporally and spatially. The impact plate itself should not be positioned in the region of the free jet's transition height. Increasing the frequency of the synthetic jet has a greater influence on the heat transfer compared to an increase in amplitude. The maximum cooling performance is achieved for all jet configurations with moderate distances between the orifice and the impact plate. In this case, the jet reaches its highest mass flow and impulse and its lowest temperature.
UnivIS-Import:2018-09-11:Pub.2018.tech.ITC.stmmec.numeri
Keywords: Flow (Dynamics); Heat; Temperature; Heat transfer; Cooling; Jets; Turbulence; Vortices; Simulation; Impulse (Physics)